MULUDAN AND HADRAH: A LIVING TRADITION AND YOUTH IDENTITY IN PABUARAN, SUBANG - Reihan Irsyad Maulana; Ezra Taghribirdi Assiddiqi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
Studies on Muludan often overlook the active role of Hadrah in shaping youth identity, frequently treating it as mere accompaniment. This research analyzes the symbiotic nexus between the Muludan tradition and Hadrah performance in Pabuaran, Subang, focusing on its function as a medium for cultural regeneration. Using a qualitative case study method, the study involved six key informants from the Markazul Anshor group, including religious authorities and youth practitioners aged 16–20. Data were analyzed through thematic coding and interpreted using Social Identity Theory and the concept of Collective Effervescence. The findings reveal a chronological transition in musical hegemony from Qasidah and Marawis to Hadrah, which has transformed into a pop culture phenomenon. Hadrah provides youth with symbolic capital and social pride, bridging the gap between sacred ritual and contemporary identity. This research confirms that Hadrah is a vital mechanism for cultural regeneration, ensuring the vitality of Islam Nusantara traditions among the younger generation in a Nahdlatul Ulama environment.